CAFF Map No.59 - The distribution of Arctic char species complex, sensu stricto, and the location of introduced populations - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2010)
CAFF Map No.59 - The distribution of Arctic char species complex, sensu stricto, and the location of introduced populations, 2010